Análisis del efecto de las condiciones climáticas en el desarrollo y producción del cultivo de sandía - Díaz Salazar, Damaris Angie (2024)
This essay deals with the analysis of the effect of climatic conditions on the development and production of watermelon cultivation. The objectives set were to detail the climatic conditions suitable for the development of watermelon cultivation and to establish the benefits of climatic conditions for the development and production of watermelon cultivation. The conclusions determined that watermelon cultivation has an important agro-socioeconomic importance along the Ecuadorian coast, particularly for the residents of the province of Manabí. However, there is a limited amount of literature available on the successful adaptation of new watermelon hybrids, particularly in terms of product quantity and quality; Ecuador has a tropical climate that is conducive to the cultivation of a wide variety of fruits, including watermelons; The presence of antioxidants like vitamin C and lycopene in watermelon helps protect our cells against free radicals and oxidative stress. Antioxidants can also improve the immune system and mitigate susceptibility to chronic diseases; The optimal temperature range for plant development is between 25 and 28°C, the optimal relative humidity for watermelon is between 60% and 80%, playing a crucial role during flowering and needing approximately 10 hours. of light per day and the optimal soil for growing watermelons is one that is deep, loose and well-drained. It is suggested that the soil be silty in texture and have a pH range of 5.5 to 6.8.